Analysis of Angry Behavior and Emotion Regulation Seen in Adolescent Gender in Upper Toundanouw Village, Southeast Minahasa - Mandagi, Klaveren G.K.; Rawis, Joulanda A.M.; Hartati, Meike E. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Angry behavior is an angry emotional response to a stimulus from the environment that is not in accordance with the wishes and is vented into negative actions to express emotions. Emotions play an important role in teenagers' social lives. As individuals who are growing and developing, teenagers tend to be irritable, irritable, easily discouraged, and prone to exploding when they feel offended. Therefore, it is important to develop the ability to manage angry emotions in adolescents. This ability to manage angry emotions is called emotional regulation. Emotional regulation is an individual's ability to accept, control and respond to emotions in an appropriate manner when under pressure. This research aims to analyze anger behavior and emotional regulation seen in adolescent gender in Toundanouw Atas Village, Southeast Minahasa. The research method used in this research was quantitative approach is a type of comparative research. The samples taken in this research were 55 people. Based on the results of data analysis in this study, it can be concluded that the difference in the tendency for angry behavior and emotional regulation in male and female adolescents is in high levels of angry behavior and low emotional regulation, which means that there is no difference in the tendency for angry behavior and emotional regulation in adolescent boys. men and women in Upper Toundanouw Village, Southeast Minahasa. The samples taken in this research were 55 people. Based on the results of data analysis in this study, it can be concluded that the difference in the tendency for angry behavior and emotional regulation in male and female adolescents is in high levels of angry behavior and low emotional regulation, which means that there is no difference in the tendency for angry behavior and emotional regulation in adolescent boys. men and women in Upper Toundanouw Village, Southeast Minahasa. The samples taken in this research were 55 people. Based on the results of data analysis in this study, it can be concluded that the difference in the tendency for angry behavior and emotional regulation in male and female adolescents is in high levels of angry behavior and low emotional regulation, which means that there is no difference in the tendency for angry behavior and emotional regulation in adolescent boys. men and women in Upper Toundanouw Village, Southeast Minahasa